(untitled) (Ticontre. Teoria Testo Traduzione, 2021)
Pavese and Pasolini are undoubtedly two of the greatest authors of XXth century Italian literature: both lovers of classical texts, from Homer to the Thousand and One Nights, they share a religious sense of life or, as Sanguineti suggest, even a Catholicism, which is both intimate and problematic, and a special love for the natural, archaic and primitive landscapes of their childhood. This article aims to investigate the reasons why Pasolini, nevertheless, speaks in derogatory terms of a possible «Pavese function». For this purpose, starting from the American dream that they both nurtured in very different forms and from some psychological and ethno-anthropological readings which they had in common, this article deals with their reflections on literature, society and the concept of myth, which in one case seems to serve primarily as an escape route, in the other seems to succumb to the principle of reality. Hence a narrative oscillation between harmony, oracularity, irrationalism on the one hand, rationality and essayism on the other.